A one-dimensional integral approach to calculating the failure probability of geotechnical engineering structures. (October 2017) - Su, Yonghua; Fang, Yanbing; Li, Shuai; Su, Ya; Li, Xiang
Abstract: This study focuses on the geotechnical engineering structures with implicit or unknown expressions of performance functions. A one-dimensional integral approach (ODIA) consisting of sampling, evaluation of statistical moments for multivariable functions, probability density function fitting, and simple integration of failure probability was developed through system integration. A convergence study of an illustrative example was conducted, and the error analysis revealed that the accuracy of ODIA is equivalent to that of the second-order reliability method. Applications of ODIA to a slope and surrounding rock of an excavation were presented to further confirm the accuracy, efficiency, and practicability of the approach.